High Dose Statins: Is it Beneficial over Conventional Dose of Statin in Acute Coronary Syndrome? - Islam, AEM M; Mazumder, AAS (Cardiovascular Journal, 2010)
Increasing burden of cardiovascular disease risk factors has led to increase in the incidence in the coronary artery disease (CAD). Advancements in medical and surgical care of patients with heart disease have led to a large number of people surviving acute coronary events. Patients with acute coronary syndrome (ACS) are at high risk for recurrent coronary events, sudden death, and all cause mortality. Conventional revascularization therapies reduce the risk of further ischaemia but do not affect the underlying atherosclerotic disease. Statins have a proven record in the secondary prevention of coronary heart disease. Furthermore, statins have been shown to exert various pleotropic effects, which may stabilize vulnerable atherosclerotic plaques. Therefore, initiating, statin therapy in patients with established CAD is both beneficial and more cost effective. Trials conducted in recent times have addressed the issue of whether higher dose statin therapy provides further reductions in the risks of cardiovascular events following an acute coronary syndrome diagnosis, over and above that provided by a conventional dose statin regimen. However, recent trials of high dose statin therapy in patients with acute coronary syndromes have yielded conflicting results. The aim of this article is to provide a critical and up-to-date summary of the findings of clinical trials of intensive statin therapy, including a brief overview of safety and efficacy of such treatments. Keywords: Statin; Acute coronary syndrome. DOI: 10.3329/cardio.v2i2.6648 Cardiovasc. j. 2010; 2(2) : 245-251